Factors that Women Consider When Choosing to Work (Case Study of the Salted Fish Processing Industry on Pasaran Island, Bandar Lampung) - Irawan, Arif; Yuliawan, Dedy (Lafadz Jaya Publisher, 2024)
The workforce in the salted fish processing industry in Pulau Pasaran Tourism Village is predominantly composed of women, particularly housewives. This industry was selected for the study due to that it has the highest number of female workers in Bandarlampung City. The objective of this study is to analyze the impact of husbands' income, workers' wages/salaries, and the number of dependents on the contribution of female workers in Pulau Pasaran. The population of the study includes female workers employed in the salted fish processing industry and living in Telukbetung Timur, Bandarlampung. The sample was taken using purposive sampling technique, consisting of a total of 37 female workers as respondents. Data were collected through observation, questionnaires, and documentation, and analyzed using descriptive quantitative methods. The results of the study indicate that family or husbands' income, wages/salaries, and the number of dependents significantly influence the contribution of female workers in the salted fish processing industry in Pulau Pasaran. This study reveals that female workers in this industry play a crucial role in increasing family income.